Effects of Knowledge and Attitude, E-Health Literacy, and Health Self-Efficacy on COVID-19 Vaccine Intention in India - Anamika Chandra; Devina Sharma; Apurvakumar Pandya; Arpit Datey; Ashu Singh (Journal of Pharmacy and Bioallied Sciences)
Background: A number of strategies were used to stop the COVID-19 worldwide pandemic. The most promising method for saving people against the pandemic proved to be vaccination. Aims and Objectives: The current study aims to determine and examine the factors influencing the intentions for COVID-19 vaccine uptake in the Indian population. Materials and Methods: Accordingly, a survey was performed to obtain information regarding attitude and intentions on vaccination against COVID-19, knowledge on vaccination against SARS-CoV-2, e-health literacy. Using Smart PLS version 4, structural equation modeling was used to analyze the data. Results and Conclusion: E-health literacy indirectly caused variance in COVID-19 vaccine intentions, whereas knowledge and attitude (β =0.685) and health self-efficacy (β =0.673) directly influenced COVID-19 vaccine intentions.